El cáncer de piel no melanoma: carcinoma basocelular. Revisión de la literatura - Rappoport, Daniel; Orchard B., Ian; González A., Tomás; Rappoport W., Daniel; Gac E., Patricio; Parada F., Vivian (Revista Hospital Clínico Universidad de Chile, 2025)
Basal cell carcinoma (BCC) is the most common type of non-melanoma skin cancer, representing 80% of cases. Its incidence has increased due to population aging and sun exposure. Although it rarely metastasizes, its high prevalence places a significant burden on healthcare systems. Risk factors include UV radiation exposure, radiotherapy, genetic predisposition, immunosuppression, skin phototype, and previous BCC history, among others. BCC is classified into histopathological subtypes such as nodular, superficial and morpheaform, each with distinctive clinical characteristics. Diagnosis is made through clinical examination, dermatoscopy, and biopsy. The main treatment is surgical excision, with options like micrographic surgery or Mohs surgery for high-risk lesions or critical locations. In selected cases, topical therapies and radiotherapy can be used. Long-term follow-up is crucial as patients with BCC have a high risk of developing new lesions. Prevention, early detection, and appropriate treatment are essential to reduce morbidity and mortality associated with BCC. Continuous efforts in education and research are needed to address this public health issue.